Temperature Characteristics of Axle-Box Bearings Under Wheel Flat Excitation - Yaping Luo; Fan Zhang; Zhiwei Wang; Chen Yang; Weihua Zhang; Fengshou Gu (Lubricants)
The high-amplitude and high-frequency wheel–rail impacts excited by wheel flat result in severe contact friction in axle-box bearing (ABB), and the friction can cause a temperature rise or even structural damage of ABB. To this end, a thermal analysis model considering the vehicle operation environment is proposed to analyze the temperature characteristics of ABB. Various coupling dynamics effects between the vehicle–track system and ABB are synergistically integrated. The heat conduction, convection, and radiation between the various components of ABB are also integrated into the thermal analysis modeling. By the field tests, the accuracy of the ABB thermal model is validated. The results obtained through the model simulation show that the ABB temperature increases with vehicle speed and wheel flat length, and the ABB temperature at the outside row is higher than that at the inside row. Moreover, the temperature of the roller, cage, inner ring, outer ring, and axle box increases following an ascending order. Specifically, the temperature at the small end of the roller is higher than that at the large end. The findings of this study can provide engineering guidelines for the condition monitoring of ABBs.